In Situ Response Time Measurement of RTD Based on LCSR Method - Yanyong Song; Yi Liang; Zhenwen Zhang; Geyi Su; Mingxu Su (Sensors)
This study aims to overcome the limitations of conventional plunge tests for evaluating resistance temperature detector (RTD) response times under actual operating conditions, particularly in confined nuclear power plant piping. An in situ measurement device based on the loop current step response (LCSR) method was developed, with a conversion relationship to plunge test results established through numerical simulation and experimental validation. Investigations in a rotating water channel (over the flow velocity range of 0.2 to 0.6) confirmed excellent agreement in RTD response time, showing only 3.78% deviation between second-order-converted LCSR and plunge test measurements at 0.6 m/s. Both methods consistently revealed reduced RTD response times at higher flow velocities, with deviations consistently within ±10%, complying with nuclear instrumentation standards (NB/T 20069-2012). The LCSR method enables reliable in situ assessment while maintaining strong correlation with laboratory plunge tests.